Atención al cliente en el “Hotel San Juan” de la parroquia san juan. - Socag Lema, Magaly Esthefania (2022)
Through this case study, the problems that the hotel has, such as the lack of staff training, lack of communication, motivation and not knowing how to listen to the suggestions and needs of the client, were made known, through this a justification was made to give know the causes and effects within the hotel, so it is important to expose the reasons that will be carried out through an in-depth analysis or survey of the subject of customer service at the "HOTEL SAN JUAN", and the benefits of this investigation is to be able to identify the factors that influence in order to analyze and obtain a solution for said problem. We were able to set objectives as well as specific general ones to have a clear objective of what we want to achieve through this research, we also make known what the line and subline are to which our work is related, within the conceptual framework it allows us to investigate different authors who tell us about customer service. The methodological market helped us to identify what type of research to use, what methods, techniques and instruments to carry out for said work. Finally, we make known what the conclusions and recommendations are that will help us to conclude with the factors that affect customer service.